Exploring the Relationship between Trust, Academic Service Quality, and Student Satisfaction in the Faculty of Teacher Training and Education - Lokolo, ‪Lamberthus J; Kempa, Rudolf; Rehatta, Geradin; lasaiba, Mohammad Amin (AL-ISHLAH: Jurnal Pendidikan, 2024)
Student satisfaction refers to the level of contentment experienced by students regarding various aspects of their educational experience, including the quality of academic services and student trust in development opportunities. This satisfaction is an essential indicator of educational institutions' success in meeting students' expectations and needs. This study aims to analyze and understand the determinants of student trust and the quality of educational services (tangible, empathy, reliability, responsiveness, assurance) on student satisfaction at the Faculty of Education and Teacher Training (FKIP) of Pattimura University, Ambon. This study adopts a quantitative approach to explore the relationship between independent and dependent variables. Utilizing a simple random sample, every member of the population has an equal chance of being selected from the 120 respondents analyzed using SPSS version 27. The hypothesis testing shows that Student Trust, Tangible, Reliability, Responsiveness, and Assurance were accepted; Empathy was rejected. Independent variables influence 56.1% of the dependent variable. The abstract's conclusion states that the independent variables explain 56.1% of the variation in the dependent variable, student satisfaction. Elaborate slightly on what this implies about the relationship between service quality dimensions and student satisfaction.